QUALITY MANAGEMENT OF WATERS OF THE DANUBE LAKES ON EXAMPLE OF THE YALPUG-KUGURLUY LAKE - Котова, Т. В. (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2014)
The paper presents the results and used mathematical models for solving water and freshwater ecological status (on example of the Ialpug-Kugurluy lake of Danubian lake system). An urgent task control incoming and outgoing components of the water balance of lakes in order to establish the optimal markers for maintaining the quality of water in the reservoirs was considered. Schedule changes in salinity for the Yalrug-Kugurluy lake was built for the time interval 1974 - 2011 years. The water balance equation for this reservoir was proposed.